Influencia en la separación de los padres en el desarrollo del trastorno negativista desafiante en los niños de la Escuela Fiscal Mixta Prof. Sosena Barrezueta de Zamora periodo lectivo 2013-2014. - Cortez López, Jessica Sugey (2015)
The thesis research theme "Influence in the separation of parents in the development of oppositional defiant disorder in children Prof. Sosena Barrezueta Mixed Fiscal School of Zamora academic year 2013-2014 " . The interest in investigating this problem is based on knowing the reality of parental separation and the effects that interfere with the development of Oppositional Defiant Disorder aimed at strengthening communication between partners , and thus improve relationships with their children, and thus achieve adequate school performance , designing methodological strategies to improve the weaknesses and personal problems.